Betatron Application in Mobile and Relocatable Inspection Systems for Freight Transport Control; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Chakhlov S. V. Sergey Vladimirovich; Kasyanov (Kas'yanov) V. A. Valery Alekseevich; Osipov S. P. Sergey Pavlovich; Shtein M. M. Mikhail Mikhailovich; Stein A. M. Aleksandr Mikhailovich; Sun Xiaoming (2016, 2016)
Title screen